IFN-γ signaling is required for the efficient replication of murine hepatitis virus (MHV) strain JHM in the brains of infected mice - Catherine M. Kerr; Macie A. Proctor-Roser; Srivatsan Parthasarathy; Joseph J. O’Connor; Jessica J. Pfannenstiel; Robin C. Orozco; Anthony R. Fehr (PLoS ONE, 2025)
Neurotropic viruses are a major public health concern as they can cause encephalitis and other severe brain diseases. Many of these viruses, including flaviviruses, herpesviruses, rhabdoviruses and alphaviruses enter the brain through the olfactory neuroepithelium (ONE) in the olfactory bulbs (OB). Due to the low percentage of encephalitis that occurs following these infections, it’s thought that OBs have specialized innate immune responses to eliminate viruses. Murine hepatitis virus strain JHM (JHMV) is a model coronavirus that causes severe encephalitis and can access the brain through olfactory sensory neurons. We’ve shown that a JHMV Mac1-mutant virus, N1347A, has decreased replication and disease in the brains of mice. Here we further show that this virus replicates poorly in the OB. However, it is unknown which innate immune factors restrict N1347A replication in the OB. RNA-seq analysis of infected olfactory bulbs showed that IFNγ was upregulated in the OB while IFN-β was barely detectable at 5 days post-infection. To determine if IFN-γ restricts JHMV N1347A replication, we utilized IFN-γ and IFN-γ receptor (IFN-γR) knockout (KO) mice. Surprisingly we found that JHMV WT and N1347A replicated very poorly in the OB and whole brains of both IFN-γ and IFN-γR KO mice following intranasal infection, though survival and weight loss were unaltered. Furthermore, we determined that microglia, macrophages, and CD4 + T cells were the primary cells producing IFN-γ during the early stages of this infection. We conclude that IFN-γ is required for the efficient replication of JHMV in the brains of infected mice.